(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article discusses the use of technology and technological tools in teaching and learning languages by means of innovative tools and resources that enhance the educational experience.